2011
DOI: 10.1111/j.1752-1688.2011.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Analysis of a Collaborative Watershed Management Process: A Florida Case Study1

Abstract: This study focuses on a Florida watershed where development of a total maximum daily load (TMDL) and its implementation plan resulted in conflicts among stakeholders. The overall goal is to build a better understanding of stakeholder perceptions of water quality problems, water policy processes and decisions, and water management plan development in a region where these issues have become contentious. Findings are based on a stakeholder analysis using qualitative data collected through focus groups with agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…In a study focused on developing a water management plan in Florida, Borisova et al (2012) designed a collaborative process to build a better understanding of stakeholder perceptions of water quality problems and water policy. The authors found that stakeholder conflicts were associated with perceived flaws in the structural and procedural characteristics of the stakeholder engagement process (e.g., suboptimal watershed stakeholder representation on committees, limitations in information sharing between stakeholder groups).…”
Section: Discussionmentioning
confidence: 99%
“…In a study focused on developing a water management plan in Florida, Borisova et al (2012) designed a collaborative process to build a better understanding of stakeholder perceptions of water quality problems and water policy. The authors found that stakeholder conflicts were associated with perceived flaws in the structural and procedural characteristics of the stakeholder engagement process (e.g., suboptimal watershed stakeholder representation on committees, limitations in information sharing between stakeholder groups).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of sources, including agriculture, urban-related runoffs, and municipal discharges, contribute to the impairments (USEPA, 2012c). However, opinions about nutrient and pathogen impairments can differ among various stakeholder groups (e.g., Borisova et al, 2012b). In this article, we specifically examine the differences in opinions about nutrient and pathogen water pollution among respondents (a) living in rural and urban areas; (b) with different demographic characteristics based on age, gender, and education; and (c) supporting eco-centric or anthropocentric worldviews.…”
mentioning
confidence: 99%
“…Such factors as the compatibility of the BMP with producers' beliefs, values, and self-image can play a decisive role, especially when the difference in the payoffs for alternative production practices is relatively small (i.e., the case with the flat payoff function) (Pannell, 2006;Pannell et al, 2006). BMPs are a cornerstone of agricultural water quality policy, and producers' perceptions about the development and administration of the policy can also affect the choice to adopt a specific production practice (Borisova et al, 2012;Lubell, 2004;Sabatier et al, 2005). For example, the fact that BMP adoption is mandatory in Florida implies that producers' beliefs about the role of government in regulation of private actions can affect the decision to comply or not with the BMP program (Lubell, 2004).…”
Section: Main Results Implicationsmentioning
confidence: 98%